The Values of Pancasila Democracy in Direct Regional Head Elections - Puspaningrum, Puspaningrum; Agatha Jumiati (Indonesian Journal Publisher, 2025)
This research aims to examine how the values of Pancasila democracy are applied in direct regional elections. The background of this research is that direct regional elections have been held since 2005, whereas previously regional elections were chosen by the Regional People's Representative Council (DPRD) of the regency/city. This research is a normative legal study that examines the norms present in the regional election regulations, analyzed through the values of Pancasila. The data used is secondary data, which is obtained through library research sourced from primary legal materials as well as secondary legal materials, namely the Law. The latest regional head election law is Law No. 10 of 2016, and the most recent one is Law No. 6 of 2020 concerning the stipulation of Government Regulation in Lieu of Law No. 2 of 2020 on the Election of Governors, Regents, and Mayors. The concept of direct regional elections emerged as a result of Law No. 22 of 2007 concerning the Administration of General Elections. This law included regional elections within the electoral regime, officially naming them General Elections for Regional Heads, abbreviated as PEMILUKADA. After further examination, it was found that regional elections are not included in the electoral regime because the basis of regulation in the 1945 Constitution is different. General Elections are regulated in Article 22 letter E, while Regional Head Elections are regulated in Article 18 paragraph 4. Which states,